Barron's GMAT - Umar M.B.A., Bobby (Barrons Educational Series, 2017)
Barron’s GMAT is designed to give you the best balance in both the depth of content and breadth of strategies. Written by two of North America's leading GMAT experts and award-winning instructors, this edition gives you the confidence to tackle every GMAT problem. You will know what to expect, what theory each question tests, what strategies you have in your arsenal and the step-by-step processes to get the correct answer quickly and efficiently.